Construction and test of a small-pad resistive Micromegas prototype - Alviggi, Mariagrazia; Canale, V.; Pietra, M. Della; Oliveira, R. De; Donato, C. Di; Farina, E.; Franchino, Silvia; Iengo, P.; Iodice, M.; Petrucci, F.; Rossi, E.; Sekhniaidze, G.; et al. (Journal of Instrumentation, 2018)
Resistive Micromegas are nowadays a mature technology for High Energy Physics experiments. In the ATLAS experiment at CERN these detectors will operate at hit rates up to 15 kHz/cm2. Future upgrades of existing experiments and new detectors at future accelerators will require operation at rates up to three orders of magnitude higher. In this paper we present the design, construction and test of a Micromegas with a pad resistive readout of few mm2 in size. We aim at precision tracking in high rate environment without efficiency loss up to tens of MHz/cm2. The detector layout and the construction technique are described, along with a characterisation of its performance, carried out by means of radioactive sources, X-rays and high energy particle beams.
Gesehen am 11.05.2020